Reported bruxism and biopsychosocial symptoms: a longitudinal study - Ahlberg J, Savolainen A, Rantala M, Lindholm H, Ko¨no¨nen M. (Blackwell Synergy, 2004)
In this follow-up study of 30–50-year-old employees (n ¼ 211) of the Finnish Broadcasting Company (YLE), respondents completed questionnaires in both 1999 and 2000 containing items on demographic data, tobacco use, levels of perceived bruxism, affective disturbance, sleep disturbance, somatic symptoms, pain symptoms and temporomandibular disorder (TMD) symptoms.